The Influence of Product Innovation and Price Perception on Coffee Purchasing Decisions on the Aerocoffeenery Soreang Online Platform Application - Ismara, Hernandi; Jaya , Rama Chandra (Dinasti Publisher, 2024)
The purpose of this study was to determine the effect of Product Innovation and Price Perception on consumer purchasing decisions on the Coffee Online Platform Application Aerocoffeenery Soreang both partially and simultaneously. The population in this study were consumers and customers at Coffee Online Platform Application Aerocoffeenery Soreang, with a total of 100 samples. The sampling technique used in this study was a non-probability sampling technique. The method used in this research is Quantitative Method with the data collection technique used is interviews and distributing questionnaires to respondents. The data analysis technique used is multiple linear regression with the SPSS program. The results of the study concluded that: (1) Product Innovation has a positive and significant influence on Purchasing Decisions. (2) Price Perception has a positive and significant influence on Purchasing Decisions. (3) In simultaneous testing, Product Innovation and Price Perception have a positive and significant influence on purchasing decisions for consumers and customers of the Coffee Online Platform Application Aerocoffeenery Soreang. The magnitude of the influence of Product Innovation and Price Perception is indicated by the Adjusted R Field value of 74.8% and the remaining 26.2% is influenced by other variables not examined in this study.